The Relationship Between Work Life Balance, Work Motivation and Employee Engagement Towards Job Satisfaction: A Study Among Aviation Workers in Malaysia - Nur Earma Farhana, Zulkifli (2023)
With today's market competition, every company will do their best to protect its assets, particularly those that are vital to the aviation sector. Thus, the primary objective of this research is to investigate the relationships between work life balance, work motivation and employee engagement towards job satisfaction among aviation workers in Malaysia. A total of 183 respondents were involved in this study via quantitative research method and the data were examined by utilizing the Statistic Package for Social Science (SPSS). The results of study reveal that work life balance, work motivation and employee engagement have a significant correlation with job satisfaction with (r = 0.501, p = 0.001), (r = 0.464, p = 0.001) and (r = 0.653, p = 0.001). However, the study concludes that only work life balance, and subscales of employee engagement (vigor and dedication) is a significant predictor and contributor to job satisfaction among aviation workers in Malaysia